Assessing the risk of COVID-19 in Nepal - Koo, Jawoo; Azzarri, Carlo; Ghosh, Aniruddha; Quabili, Wahid (International Food Policy Research Institute, 2021)
As COVID-19 vaccines are becoming available, governments will need to assess the number and location of the most vulnerable people within their populations. However, problematically, tracking data for most low- and middle-income countries are only available at the national level. To support the COVID-19 relief effort, the Gender, Climate Change, and Nutrition Integration Initiative (GCAN) was commissioned to develop a subnational dataset of key COVID-19 risk indicators and potential risk hotspots.